PENGARUH WAKTU PENYIMPANAN SAMPEL TERHADAP HASIL ANALISA NIKEL (Ni) PADA BIJIH LATERIT MENGGUNAKAN ALAT XRF - Gustan, Azhari; Iryani, A. Sry; Riza Basalamah, Faisal (UIR Press, 2026)
This study aims to determine the effect of sample storage time on the results of nickel (Ni) content analysis, determine changes in physical characteristics in the form of water content during storage, and evaluate the level of analysis accuracy using the X-Ray Fluorescence (XRF) method. The study was conducted with variations in storage time of laterite nickel ore samples for 0 weeks, 1 week, 2 weeks, 3 weeks, and 4 weeks. The prepared samples were analyzed using XRF without reheating to maintain natural conditions after storage. The parameters observed included nickel (Ni) content, water content, and deviation of analysis results. The results showed that the nickel content decreased from 1.88% in week 0 to 1.75% in week 4. Meanwhile, the water content increased from 0.30% to 1.25% as storage time increased. This increase in water content was influenced by the hygroscopic nature of laterite ore which absorbs moisture from the environment. In addition, the deviation value of the analysis results increased from 0.00% to 0.13%, which indicates a decrease in the accuracy of XRF analysis due to changes in the physical condition and matrix of the sample. Based on the research results, the recommended optimum storage time is a maximum of 1 week, because under these conditions the water content is still below the ideal limit (<1%) and the deviation of the analysis results is relatively small so that the results are still representative.